The Pragmatics of Theatrical Dialogue: Analysing Utterance and Meaning on Stage - Ali Al-Fuadi, Mohammed Ahmed (International Journal of Mass Communication, 2025)
The use of dialect in personal communication extends beyond merely sharing thoughts and information; it plays a vital role in fostering and shaping relationships among individuals. Conversations enable people to express their identities, cultural ties, and preferences for intimacy or distance within their relationships, often without conscious awareness. By employing specific dialects, individuals define their relationships and reaffirm their connection to particular social groups. In contrast, inappropriate terms of address can obstruct effective communication, as these terms mirror the social dynamics of status and distance between speakers, as noted by Akindele (2008: 3-15). The phonetic elements of communication seldom convey neutral implications for interpersonal relationships. Ultimately, self-expression communicates distinct emotions and mental states, which can significantly influence the outcomes of interpersonal interactions. This article aims to outline the features of a written theatrical text that emphasises its oral intent, especially regarding its suitability for stage performance. By highlighting a linguistic understanding that goes beyond the basic levels of words, clauses, phrases, and sentences—knowledge that is essential for effective communication—this study will explore pragmatics from multiple perspectives. This includes analysing speech acts through a focused linguistic approach and interpreting pragmatic significance using frameworks drawn from sociolinguistics, conversation analysis, discourse analysis, and the ethnography of speaking, among others. The research employed qualitative assessment through established linguistic methodologies and utilised descriptive qualitative methods for data analysis. Data collection involved observing and listening to character interactions during performances, as well as examining the corresponding scripts.